2017
DOI: 10.3126/bibechana.v15i0.18688
|View full text |Cite
|
Sign up to set email alerts
|

Sources and causes of water pollution in Bangladesh: A technical overview

Abstract: Water pollution is one of the significant dangers to general wellbeing of Bangladesh. Drinking water quality is inadequately overseen and checked. Bangladesh positions at number 86 among 142 countries with respect to drinking water quality. Drinking water sources, both surface and groundwater are debased with coliforms, harmful metals and pesticides all through the nation. Different drinking water quality parameters set by WHO are every now and again damaged. Human wastes, transfer of civil and mechanical wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Newaz et al., 2020 found higher concentrations of heavy metals in roadside sediments [ 63 ]. Agricultural crops grown in urban roadside area accumulate higher amount of toxic metals [ 15 , 49 , 64 , 65 ]. Furthermore, Bangladesh have almost 6000 registered and numerous unregistered brick field and most of them established on the river bank area.…”
Section: Sources Of Water Pollution In Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation
“…Newaz et al., 2020 found higher concentrations of heavy metals in roadside sediments [ 63 ]. Agricultural crops grown in urban roadside area accumulate higher amount of toxic metals [ 15 , 49 , 64 , 65 ]. Furthermore, Bangladesh have almost 6000 registered and numerous unregistered brick field and most of them established on the river bank area.…”
Section: Sources Of Water Pollution In Bangladeshmentioning
confidence: 99%
“…Farmers using this polluted water for irrigation made the toxic materials to enter into the food chain and ultimately come to human. The poor usually use this polluted water for washing and cooking, which is very harmful [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…On contrary to that, Non-point sources are diffused in nature which is difficult to screen and control, like waste water running over agricultural field, leakage of oil from boats. Some common examples are shown in the table below [1,15].…”
Section: Causes Of River Pollutionmentioning
confidence: 99%
“…And this pollution is expanding day by day destroying the waterways. This low quality water and water scarcity is associated with the reality that this pollution decreases the water supply and increases the financial burden to make it useable [1].…”
Section: Introductionmentioning
confidence: 99%
“…Reza et al in his research compared different electricity production techniques and found nuclear generation to be more suitable for Bangladesh to meet annual load demand. He showed Bangladesh lacks a huge power demand and RNPP can fulfill this demand [6]. Mollah et al reviewed present power generation technologies of Bangladesh and made an analysis on how RNPP will be environment friendly; specially pointed acute analysis on nuclear waste disposal in an ecofriendly manner [7].…”
Section: Literature Reviewmentioning
confidence: 99%